ELIPSIS DALAM KUMPULAN CERPEN KAMI NO KODOMOTACHI WA MINA ODORU KARYA HARUKI MURAKAMI - Saraswati Wangsa, Putu Dian (Humanis, 2013)
This research was analyzing about word clauses absorption on story and their influences to the essence of the story.  The data sources were mostly taken from some short story by Haruki Murakami entitled “Kami no Kodomotachi wa Mina Odoru”. The results  of  the  undergone  research showed that  the  absorption  of  the  texts  could  be separated  into  two  absorption,  the  meaning  and  essence,  and  the  absorption  in conversation. The absorption in conversation known as noun absorption which was the nouns or subjects that followed by ‘wa’ or ‘ga’, in fact, were the focus of the sentence. Ellipsis in some conversation also indicated by absorpting the understandable words or phrase that had been talked before the texts context or depend from the situations of the speaker and his conversation partner. The last ellipsis, main sentence ellipsis occurred when some phrases or words were decided to be the main part of a conversation.
Keywords: ellipsis, subject, conversation